Decontamination pig carcasses of organic acids with commercial and saline acidified ultraviolet light - De Carli, Eliane Maria; Terra, Nelcindo Nascimento; Fries, Leadir Lucy Martins; Menezes, Cristiano Ragagninde; Palezi, Simone Canabarro (Semina: Ciências Agrárias, 2013)
In Brazil the consumption of pork has increased significantly in recent years, mainly due to large public awareness campaigns, especially in relation to issues of concern for consumer health. The meat quality is the factor to be controlled so that the consumer can enjoy the benefits. There are many variables to be controlled. Aiming to reduce the contamination and increase the shelf life of pork were performed nine treatments with mixtures of organic acids, saline acidified, exposure to ultraviolet light and water at 80 º C during 30 days of storage, belly pork, and all analyzes performed in triplicate. Counts were performed aerobic mesophilic microorganisms, psychrotrophic, total and fecal coliforms, Salmonella, pH determination and the number of thiobarbituric acid reactive substances (TBA) sensory evaluation. Showed a reduction in the contamination of pork belly cuts with a mixture of organic acids, followed by exposure to ultraviolet light for 1 minute. Regarding the pH treatments that were added to the mixture of organic acids differ from the other treatments except the control. The solutions of organic acids did not affect the sensory characteristics of pork roast. Through the experiments in this study, it was concluded that we can make further proposed as an alternative for industrial meat mixture obtaining a greater microbiological control features without changing the feedstock, increasing the life and thereby offering the consumer a quality product and commercially safe.